Critical analysis of the current model of financial accounting of innovation capital and the ways of its development - V.K. Makarovych (Економіка, управління та адміністрування)
The need to improve the current model of innovative capital accounting in the conditions of the formation of the knowledge economy has been grounded. The existing approaches to the recognition of internally created intangible assets in S(S)BO 8 «Intangible assets» and in IFRS 38 «Intangible assets» have been analyzed. The criteria for recognition / non-recognition of the company’s developments as internally generated intangible assets have been analyzed according to IFRS 38. The differences between IFRS and other national and international accounting models in accounting and recognition of research and development have been disclosed. The problems of abuse by the subjects of the accounting organization during the capitalization of the company’s products have been highlighted. The existence of a mixed accounting model for intangible assets in IFRS has been grounded. Two options for the development of the current research and development accounting model, currently implemented in IFRS and NS(S)BO, were formed (improvement of the system of criteria used for the recognition of developments based on the position of progressivism; disclosure of more detailed information about the reasons for the decision in the notes to the financial statements on development capitalization).